Finding graves in a cemetery: Preliminary forensic GPR investigations in the Non-Catholic Cemetery in Rome (Italy). (February 2016) - Barone, P.M.; Swanger, K.J.; Stanley-Price, N.; Thursfield, A.
Highlights: The forensic geophysical tools are relevant for archaeological and cultural purposes. The ancient cemetery GPR mapping has correctly located unknown graves. The better interpretation of its subsurface facilitates the cultural management. Abstract: This paper presents partial results of a Ground-Penetrating Radar (GPR) survey conducted in the oldest section of the Non-Catholic Cemetery in Rome (Italy). This cemetery, a unique spot within the walls of Rome, has been the principal burying-ground for non-Catholic foreigners for the past three centuries. Extensive information exists about the oldest burials in the Cemetery: many were marked by headstones or horizontal stone markers carrying inscriptions; others are recorded in literary sources but their precise locations are unknown. Moreover, the headstones and markers can be lost or misplaced as time passes. GPR survey therefore plays an important role in non-destructively investigating the subsurface of the cemetery. This is the first time that such a geophysical survey has been conducted at this site. Using a GPR system specifically designed for forensic purposes, it has helped to determine whether the grave records for the oldest part of the cemetery are consistent. In the case study reported here, the effectiveness of the technique is demonstrated by reference to a single, anomalous stone monument.